Development of A Time and Cost Control System For The Construction of A Ø1000 Mm Pipe Bridge Based on A Work Breakdown Structure (WBS) Integrated With A 3d Model and Bim to Improve Time and Cost Performance - Ulya Ilmi Azhara; Leni Sagita Riantini Supriadi; Yusuf Latief (International Journal of Science and Environment (IJSE), 2026)
The construction of large-diameter pipeline bridges plays a strategic role in ensuring the reliability of clean water distribution systems. Nevertheless, such infrastructure projects frequently experience cost overruns and schedule deviations caused by fragmented scope definition, limited integration between planning and cost control, and conventional quantity take-off practices that rely heavily on two-dimensional drawings. These limitations reduce the effectiveness of project monitoring and delay corrective decision-making during construction. This study develops an integrated time and cost control system by embedding a standardized Work Breakdown Structure (WBS) into a 3D and 5D Building Information Modeling (BIM) environment for a Ø1000 mm pipeline bridge project. A mixed-method research approach was adopted, combining expert validation, project document analysis, and quantitative assessment. Project performance was evaluated using Earned Value Management (EVM), while Partial Least Squares–Structural Equation Modeling (PLS-SEM) was applied to examine the causal relationships between WBS integration, 3D modeling, BIM implementation, the time and cost control system, and schedule and cost performance. The results demonstrate that BIM-derived quantities and costs are more consistent and traceable than those obtained from conventional Bill of Quantities (BOQ) calculations, particularly for steel structural and support components that exhibit the highest cost deviations. The integration of WBS with BIM 3D and BIM 5D significantly strengthens activity-level monitoring, improves cost control accuracy, and enables earlier detection of schedule and cost deviations. The proposed framework provides practical decision support for proactive time and cost management in infrastructure construction projects.